Conceptual framework for food systems for diets and nutrition: Country food system fact sheet: Bangladesh - CGIAR Research Program on Agriculture for Nutrition and Health; Lecoutere, Els; Trijsburg, Laura; Vignola, Raffaele; Mekonnen, Daniel Ayalew (International Food Policy Research Institute, 2021)
This fact sheet is organized to reflect the status and/or trends of different components in the framework for food systems for diets and nutrition based on a selection of indicators for each of the domains. The indicators have been selected for their orientation toward the goal of better quality diets; their contribution to assessment of the situation at national scale; their standardized use of data and method of construction which permit crosscountry comparison; their construction based on routinely collected, publicly-accessible data or reports available for a wide range of countries. The latter implies most indicators are based on data housed by international organizations rather than national statistics.